(untitled) (Arsi Journal of Science and Innovation, 2024)
The purpose of this study was to assess the implementation of contextualvocabulary teaching in EFL (English as a Foreign Language) class. Gradetwelve English teachers and students in Adama Hawas Preparatory Schoolwere the participants of the study. Qualitative method was employed to conductthe study and such instruments as classroom observation, textbook analysis,interviews and focus group discussions were used to collect the data.einterview; textbook analysis was used to assess whether the text had enoughinstruction which enables teachers help students learn the vocabulary from theclassroom observation. Added to this, focus group discussion was used toed todevelop from contextual vocabulary instruction. Thus, the findings indicate thatteachers include contextual vocabulary instruction in EFL classes to teachvocabulary. However, context-based vocabulary instruction has not been giventhe attention it deserves in grade twelve English textbook; the activities whichare presented in matching formats also lack adequate depth.Thereforechance of learning new words from context is limited both in quantity andquality. What students want to implement in the actual classroom teachingbackground knowledge and mother tongue influence (students tend to directlytranslate the meaning of the word into their mother tongue) were also factorsthat impede contextual vocabulary teaching practice. The vocabularyinstructions should be presented to help students understand the meaning ofnew words in multiple contexts. Therefore, students should be exposed forcontextual vocabulary instruction in order to develop their word power thatenables them comprehends the concept of any text